Study on dynamics of vibrator baseplate at low and high frequencies - Zhiqiang Huang (Journal of Vibroengineering, 2017)
In order to figure out the dynamics response of vibrator baseplate and why baseplate performs poorly at high frequencies, a finite element model of vibrator-ground is developed to analyze acceleration, deformation and decoupling of the baseplate at low and high frequencies. Results show that the acceleration at low frequencies is in accordance with the function of hydraulic pressure. On the contrary, the acceleration at high frequencies is irregular and fluctuant. Within the bandwidth, the maximum deformation locates in the central area, and the baseplate deformation in long-axis direction is greater than that in minor-axis direction. Compared to low frequencies, dynamics response at high frequencies suffers response delay, and the vibrator structure is very sensitive to asymmetry, resulting in warping and waveform deformation. Baseplate experiences decoupling at both low and high frequencies, however, the decoupling at high frequencies occurs more frequently, which leads to more serious distortion. It is also found that symmetrical structure is helpful for reducing negative deformation. In conclusion, high fluctuation of acceleration, response delay and harmonic caused by complicated deformation and decoupling distortion reduce the quality of output signal and block the bandwidth towards high frequencies.